From the «Desarrollismo» to the «Enthusiasm»: Notes on Spanish Art inTransition Times - Juan Albarrán Diego (FahrenHouse, 2008)
In this paper we are intending to do a brief survey of the Spanish artistic panorama from, nearly, the end of the development economic policies («des- arrollismo», 1968) to the definitive stablishment of the democracy with the PSOE first electoral victory (1982). We will take as a main reference the research perspectives ope- ned by several editorial and exhibition projects which, recently, have questioned the paradigmatic condition of the Spanish democratic transition, arguing that this process conclude with a self conversion of the dictatorial politic structures that had obstructed the stablishment of a participative and genuine democratic system. In the artistic field, Franco ́s dead have been understood as a point of inflexion that subtracts part of the politic validity to the anti-franquist practices developed in the borders of conceptual art. This interpretation also legitimizes a return to order embodied in non-politic pain- ting trends that, supported by their market success, concealed an extremely reactionary attitude. Key words: Conceptual art, Cultural policies, Democratic transition, Enthusiasm, Movida.